EVALUATION OF TENDENCY TO SELECTION TYPE OF DELIVERY OF LASTTRIMESTER PREGNANT WOMEN REFER TO GYN CLINIC OF YASUJ CITY ON 2017 - H. M., AbadNazir1; A. H, . Motlagh2; M. A., . Ghatee3; H., Nouradin (university of eloued جامعة الوادي, 2018)
We conclude the major factors that effect on selection type of delivery were physician recommendation, husband recommendation, husband educational level, pervious type of delivery and having information about NVD and CS. The major tendency toward CS was fear of pain of NVD. Perennial injury of NVD was one of the important cause of tendency toward CS. Therefore physicians, nurses and midwifes have to give more information about NVD and CS to pregnant women and her husbands.
artical
Keywords: Cesarean section, normal vaginal delivery, pregnant women, third trimester